STRATEGI KOMUNIKASI FKUB DALAM MEMELIHARA KERUKUNAN UMAT BERAGAMA DI PROVINSI BALI - Redi Panuju; I Wayan Kontiarta (Commed : Jurnal Komunikasi dan Media, 2018)
The consequences of several Bomb incidents that allegedly carried out by terrorists who hide behind certain religions have led to the emergence of mutual prejudices among the people. Especially in the province of Bali who had experienced the tragedy of the explosion Bomb twice from two thousand two to two thousand five. The notion that the atmosphere among religious life is threatened by religious prejudices. Moreover, media coverage tends to frame the events of terror is always done by hard-line Islamic groups, it is possible that people at the lower level generalize all Muslims tend to be radical. One institution that seeks communication between religious communities is the Forum Kerukunan Umat Beragama (FKUB), whose existence in the province of Bali is very strategic. This article reviews the communication strategies undertaken by FKUB. The research method used is field research by interviewing FKUB figures as key informants. As a result FKUB's strategy contributes to maintaining community harmony, so that at the grassroots level Balinese people remain harmonious.